2022
DOI: 10.3390/ijerph19106022
|View full text |Cite
|
Sign up to set email alerts
|

Use of Information and Communication Technology by South Korean Occupational Therapists Working in Hospitals: A Cross-Sectional Study

Abstract: The convergence and development of information and communication technology (ICT) have brought changes to occupational therapy practices, posing novel challenges for occupational therapists (OTs). This study aimed to investigate current practices of ICT use and factors affecting the clinical use of ICT among Korean OTs. An online survey was conducted among 158 domestic OTs working in hospitals. Participants reported that the therapeutic use of ICT positively affected client outcomes, ICT choice, and continued … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…The thesis here is that a school's capacity to implement an effective online learning program is influenced by the availability of an ICT policy. Using digital devices and ICT successfully to promote teaching and learning may also depend on schools' policies and practices, as argued by Hwang et al (2022) [21] in the Framework. [22] conclude that clear policy, strategy, and implementation instructions are necessary to facilitate effective e-learning in educational institutions and provide more support for this position.…”
Section: -1-how Information and Communication Technology Can Help Edu...mentioning
confidence: 99%
See 1 more Smart Citation
“…The thesis here is that a school's capacity to implement an effective online learning program is influenced by the availability of an ICT policy. Using digital devices and ICT successfully to promote teaching and learning may also depend on schools' policies and practices, as argued by Hwang et al (2022) [21] in the Framework. [22] conclude that clear policy, strategy, and implementation instructions are necessary to facilitate effective e-learning in educational institutions and provide more support for this position.…”
Section: -1-how Information and Communication Technology Can Help Edu...mentioning
confidence: 99%
“…The current technology condition in classrooms indicates the education system's preparedness. Hwang et al (2022) [21] found that there are often considerable differences in life expectancy between people of different socioeconomic backgrounds. It was discovered that only people from affluent backgrounds have access to the internet at home, making online education unavailable to them.…”
Section: -1-how Information and Communication Technology Can Help Edu...mentioning
confidence: 99%